Design and development of a portable attendance / response-ware system - Chua, Sherwinna (Nanyang Technological University, 2022)
University often hold large scale events, that would benefit immensely from a platform that allows the public to express feedback and post their question in real time, this is comparable to the popular web-based ResponseWare program. The goal of this project is to design and construct a low-cost portable system that does not rely on pre-existing infrastructures like power supply or internet connection. In addition, the suggested system must meet consistency, scalability, and fault tolerance criteria. This project designs a system with a peer-to-peer architecture model, and it is constructed with several Raspberry Pi single-board computers that acts as a low powered mobile computing node. The B.A.T.M.A.N. advanced (batman-adv) module was utilized to create a mesh network that connects all of the cluster's nodes, and Apache Cassandra is employed as a distributed data storage solution with high availability and scalability. To fulfil requests from non-mesh client devices, a Python web server was created. During testing, the finished system was demonstrated to have met all the objectives and specifications.